Predictive Factors for Early-Onset Seizures in Patients With Cerebral Venous Sinus Thrombosis - Mu, Shuwen; Li, Jun; Lin, Kunzhe; Fang, Yi; Lin, Feng; Li, Ziqi; Xu, Yongjun; Wang, Shousen (Frontiers in Neurology, 2022)
Seizures are reported to be important factors contributing to poor prognosis in patients with cerebral venous sinus thrombosis (CVST). However, the predictive factors for concurrent early onset seizures in patients with CVST remain unclear. To identify the predictive factors of early seizures in patients with CVST, this study retrospectively evaluated the clinical data of patients diagnosed with CVST at two centers from January 2011 to December 2020 and analyzed the relationship between admission characteristics and early onset seizures. A total of 112 CVST patients (63 men and 49 women; mean age 39.82 ± 15.70 years) were enrolled in this study, of whom 34 (30.36%) had seizures. For patients with seizures, cerebral hemorrhage, cortical vein thrombosis, anterior superior sagittal sinus (SSS) thrombosis, middle SSS thrombosis, CVST score, modified Rankin Scale, National Institute of Health Stroke Scale (NIHSS) score, neutrophil percentage, and D-dimer level were more severe than those without seizures. Logistic regression analysis showed that cerebral hemorrhage (P=0.002), anterior SSS thrombosis (P=0.003), NIHSS score ≥5 (P=0.003), and D-dimer ≥0.88 mg/L (P=0.004) were all significant predictive factors of early-onset seizures in CVST patients. Combining the four factors further improved the predictive capability with an area under the curve of 0.871 (95% confidence interval=0.803–0.939). Further large-scale prospective studies are required to confirm these findings.